Method of Observation of Cosmic Very High Energy g-Quants by Means of Registration of Impulses of Extensive Air Showers Coherent Radio Emission - Kartashev, V. M.; Shmatko, E. S. (Видавничий дім «Академперіодика», 2013)
Method of Observation of Cosmic Very High Energy g-Quants by Means of Registration of Impulses of Extensive Air Showers Coherent Radio Emission